Identification of lncRNA competitively regulated subpathways in myocardial infarction - Wu, Xia (Exp Ther Med, 2019)
The functions of long non-coding RNAs (lncRNAs) in myocardial infarction (MI) remain largely unknown. Thus, we used the subp athway-LINCE method to characterize the potential roles of lncRNAs in MI. Candidate lncRNA-mRNA interactions were obtained from miRNA-mRNA interactions and lncRNA-miRNA interactions. Then the lncRNA and mRNA co-expression relationship pairs (LncGenePairs) were screened from the lncRNAs and mRNA intersections, which were extracted through candidate lncRNA-mRNA interactions and sample gene expression profiles. The lncRNAs in LncGenePairs were embedded into pathway graphs as nodes through linking to their regulated mRNAs, which resulted in obtaining condition-specific lncRNA competitively regulated signal pathways (csLncRPs). Finally, the csLncRPs were calculated using lenient distance similarity to obtain the lncRNA competitively regulated subpathways. Based on the statistical significance of signal subpathways, lncRNA-mRNA networks were constructed, in which hub lncRNAs were selected. A total of 65 lncRNAs competitively regulated subpathways and 13 hub lncRNAs were obtained, which associated with a risk of MI. Identifying lncRNAs competitively regulated subpathways not only provides potential lncRNA biomarkers for MI, but also helps the understanding of pathogenesis of MI.